TRANSLATION SHIFT IN GARFIELD “TAKES HIS LICKS” A BILINGUAL TEXT - Enni Maisaroh; Syahron Lubis; Sumarsih Sumarsih (Universitas Negeri Medan, 2018)
The research deals with translation shift in Garfield takes his licks a bilingual text. The objectives of the study were: (1) to find out the types of shifts in Garfield “Takes His Licks” a Bilingual Text, (2) to describe how the shifts occur in Garfield “Takes His Licks” a Bilingual Text, (3) to analyze the reasons why translation shifts occur in Garfield “Takes His Licks” a Bilingual Text. The research was conducted by using descriptive qualitative design. The data of this study were words, phrases, and clauses were translated from English into Indonesian. The data were collected through documentary technique. The technique of data analysis was interactive model. The findings of this study revealed that: (1) The category shifts in Garfield “Takes His Licks” a Bilingual Text are 1) structure shift, 2) class shift, 3) unit shift, 4) intra system shift, and 5) double types of shift. (2) There were some ways of translation shift used in Garfield “Takes His Licks” a Bilingual Text, namely grammatical change occurred, change in different word class, change in ranks and change in number. (3) There were four reasons of using translation shifts are (1) Different language systems, (2) Grammatical structures of SL do not exist in TL, (3) Literal translation is grammatically possible but may not accord with natural usage in the TL (naturalness between SL and TL) and (4) replacing virtual gap by grammatical structure.Keywords: Structure Shift, Class Shift, Unit Shift, Intra System Shift.